Role of DNA repair genes XRCC3 and XRCC1 in predisposition to type 2 diabetes mellitus and diabetic nephropathy - YEŞİL, TUĞÇE (ELSEVIER SCIENCE BV, 2019)
Introduction: Increasing number of experimental and clinical studies suggest a strong relationship between hyperglycemia, oxidative stress, DNA damage and diabetic nephropathy (DN). Also, epidemiologic studies remark an enhanced risk of cancer with type 2 diabetes. This research aims to assess whether the X-ray cross complementing group 3 (XRCC3) gene T241M polymorphism (15861539) and X-ray cross complementing group 1 (XRCC1) gene A399G polymorphism (rs25487) are related with predisposition to type 2 diabetes mellitus (T2DM) and to diabetic nephropathy in Turkish population. Materials and methods: Polymerase chain reaction-based restriction fragment length polymorphism (PCR-RFLP) was performed to identify the distribution of genotypes and frequency of alleles of T241M polymorphism of the XRCC3 gene (XRCC3 T241M) and A399G polymorphism of the XRCC1 gene (XRCC1 A399G). The study population included 238 subjects residing in Istanbul, Turkey; 116 with T2DM, 50 with DN and 72 with normal glucose metabolism. Results and conclusion: Polymorphic Gln allele of XRCC1 gene was significantly related with T2DM and DN (OR 3.09, 95% CI 1.14-8.40 and OR 3.29 95% CI 1.23-8.80, respectively) however, there was no statistical association of XRCC3 T241M with T2DM or DN. The results of this study suggest that XRCC1 399Gln polymorphism is related with an increased susceptibility to T2DM and DN in the studied Turkish population. (C) 2018 SEEN y SED. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Type 2 diabetes mellitus; Diabetic nephropathy; XRCC3 T241M; rs861539; XRCC1 A399G; rs25487; OXIDATIVE STRESS; ARG399GLN POLYMORPHISM; T241M POLYMORPHISM; BLADDER-CANCER; RISK-FACTOR; ASSOCIATION; POPULATION; METAANALYSIS; DAMAGE; SUSCEPTIBILITY